Economic and Tourism Empowerment of Rawa Pening Supported by Local Culture and Wisdom (A Study on Rawa Pening, Ambarawa) - Retnowati Retnowati; Hari Suryanto; Purwanto Purwanto; Jony Octavian Haryanto; Hanif Adinugroho Widyanto (Journal of International Conference Proceedings (JICP), 2020)
Rawa Pening Lake is a natural lake that offers a beautiful tourist destination with various kinds of food and souvenirs of Rawa Pening Lake in which these products become the superior products of the community and Local Government of Semarang Regency. Rawa Pening Lake does not only present natural beauty scenery but also provides various aquatic animals that bring economic welfare. By managing the potencies of natural resources while preserving ecosystem of the environment and the lake as well; then the community may obtain their welfare economically, socially, and culturally. This research will describe efforts of the community of Rawa Pening Lake in improving their economic and in developing tourism area of Rawa Pening Lake as the commodity for their welfare. This research uses qualitative method by using data collection technique through in-depth interview and involved observation. The community of Rawa Pening Lake becomes the main subject in the data collection. The research result shows that the dynamics of Rawa Pening Lake community in social, economic, and cultural life have important roles in realizing the improvement of economic and tourism in Rawa Pening Lake area. Community empowerment in entrepreneurship and tourism has increased the numbers of tourists who visit Rawa Pening Lake. Local culture and wisdom of the local community have supported tourism and entrepreneurship which in turns improve community welfare.